Lichen Planus Pigmentosus with Atypical Presentation- A Case Report - Akshay Patankar; Akshata A Mane; Manjaree Morgaonkar (Nepal Journal of Dermatology, Venereology & Leprology)
Lichen planus pigmentosus (LPP) is a chronic pigmentary disorder that shows diffuse or reticulated hyperpigmented, dark brown macules and patches on the sun-exposed areas such as the face, neck and other flexural folds. Clinically, it is different from classical lichen planus because LPP has a longer clinical course and it manifests with dark brown macules. In case of LPP, involvement of the scalp, nail or mucosal area is rare. The histopathological findings of the lesions show an atrophic epidermis, the presence of melanophages and a vacuolar alteration of the basal cell layer with a sparse lymphohistiocytic lichenoid infiltration. Here we report a case of lichen planus pigmentosus over sun protected areas sparing sun exposed and flexural folds.